PENGARUH KERAKTERISTIK PERUSAHAAN TERHADAP STRUKTUR MODAL: STUDI EMPIRIS DI BURSA EFEK INDONESIA - Jaladri Angleng Windraesti (Fakultas Bisnis UKDW, 2012)
The purpose of this study is to examine the influence of firm characteristics, i.e. dividend, growth sales, asset tangibility, earning volatility, and firm age on leverage as a proxy for capital structure. Samples are selected from manufacturing campanies listed on Indonesian Stock Exchange for the periode 2008-2010. Purposive sampling is used to choose the sample and 95 companies are found to be sample. Data is analyzed with test of classic assumption and examination of hypothesis with multiple linear regression method. The result shows that among five independent variables, dividend, earning volatility, and firm age are insignificant on leverage, while growth sales and asset tangibility have a positive impact towards leverage. Keywords: firm characteristics, capital structure